The great reset : Joe Biden and the rise of 21st century fascism - Beck, Glenn; Haskins, Justin (Director of the Stopping Socialism Center) (Forefront Books ; Mercury Ink, 2022)
"[The authors] use a blend of humor, storytelling, and detailed analysis to reveal for the first time the unbelievable truth about the Great Reset, tying together nearly two decades of groundbreaking research about authoritarian movements and their efforts to fundamentally transform the United States"--Flap page 1 of dust jacket.